Physiological Functions of Mcl-1: Insights From Genetic Mouse Models - Chin, Hui San; Fu, Nai Yang (Frontiers in Cell and Developmental Biology, 2021)
The ability to regulate the survival and death of a cell is paramount throughout the lifespan of a multicellular organism. Apoptosis, a main physiological form of programmed cell death, is regulated by the Bcl-2 family proteins that are either pro-apoptotic or pro-survival. The in vivo functions of distinct Bcl-2 family members are largely unmasked by genetically engineered murine models. Mcl-1 is one of the two Bcl-2 like pro-survival genes whose germline deletion causes embryonic lethality in mice. Its requisite for the survival of a broad range of cell types has been further unraveled by using conditional and inducible deletion murine model systems in different tissues or cell lineages and at distinct developmental stages. Moreover, genetic mouse cancer models have also demonstrated that Mcl-1 is essential for the survival of multiple tumor types. The MCL-1 locus is commonly amplified across various cancer types in humans. Small molecule inhibitors with high affinity and specificity to human MCL-1 have been developed and explored for the treatment of certain cancers. To facilitate the pre-clinical studies of MCL-1 in cancer and other diseases, transgenic mouse models over-expressing human MCL-1 as well as humanized MCL-1 mouse models have been recently engineered. This review discusses the current advances in understanding the physiological roles of Mcl-1 based on studies using genetic murine models and its critical implications in pathology and treatment of human diseases.